Prevention of pertussis: An unresolved problem - Susanna Esposito; Nicola Principi (Taylor & Francis Group, 2018)
Pertussis is a highly contagious respiratory disease caused by Bordetella pertussis. However, after the introduction of the whole-cell pertussis vaccine (wP), the annual incidence rates of the disease progressively declined. Despite this result, the inclusion of wP in the national immunization schedule of infants and young children was debated regarding its safety. Several efforts to produce vaccines based on B. pertussis components capable of evoking protective immunity with no or limited adverse events were made. Of these others, five pertussis antigens were considered possible components of acellular vaccines (aPs): pertussis toxin (PT), filamentous haemagglutinin (FHA), pertactin (PRN) and fimbria proteins 2 and 3. However, the introduction of aPs was followed by a slight but progressive increase in the incidence of pertussis. This paper discusses the potential reasons for reduced aPs efficacy. Moreover, it attempts to evaluate the real effectiveness of aPs and the potential differences between available preparations. Data analysis showed that several boosters are needed to maintain protection against pertussis and additional studies are needed to confirm the antigens that should be included in aPs to improve the prevention of pertussis.